Sensory diversity of a traditional Slovenian dry-cured sausages (Suha klobasa) - Demšar, Lea (Array, 2019)
Suha klobasa is a popular dry-cured sausage that is produced practically everywhere in Slovenia. The aim of this study was to investigate the main characteristics of Suha klobasa produced by different manufacturers across five different informal regions of Slovenia. Products from 31 producers, as households (11), small workshops (15) or industrial plants (3) were analysed for pH value, moisture, protein, fat, and ash, as well as for their sensory parameters, according to assessments of four profiles: appearance, texture, smell and aroma. Technological production procedures were evaluated on the basis of a survey. In average Slovenian Suha klobasa pork is used, also Suha klobasa is characterized by slow ripening and smoking or without smoking but overgrown with mould. It is always filled in a small diameter casings (32-34 mm) of the pig small intestine or permeable casings, formed in two equal-length-halves and on one side (open side) looped around, often with a wooden stick. According to the regions of Slovenia, several types of Suha klobasa can be distinguish that are defined by sausage length and surface colour, mosaic and porousness on the one hand, and acid, smoke, mould, rancid smell/aroma on the other. Suha klobasa originated from different manufacturing practices differ in visual characteristics of product (size, equality and mould), in cross-section (mosaic, porousness and glassines), and texture (hardness, toughness and integrity) but not in olfactory and aroma profile.